A look at grit: a study about Malaysian technical instructors’ performance retention - Ibrahim, Badaruddin; Mohamad, Nurul Haerani; Abd Aziz, Azlihan; Kadir, Mahadi; Abd Hamid, Zulisham (Primrose Hall Publishing Group, 2020)
The improvement of instructors' professionalism and quality should be prioritised to achieve Malaysia's Education Blueprint 2013-2025 goals. Most previous studies suggest that teacher effectiveness and performance retention could be measured by the impact of instructors on student achievement, but none of the studies measure instructors’ effectiveness and performance retention through grit, which can be an important factor in explaining achievement and persistence in maintaining expected quality of instructors’ performance. This study investigates Malaysian Technical Instructors and the grit needed to stay in the field, especially in purifying state aspirations. The purpose of this study is to describe the grittiness of technical instructors and determine if grit is associated with job performance retention based on age, education level and years of services. The data for this research was obtained through a structured questionnaire adapted from Grit-S survey and involved 88 technical instructors from the Malaysia Technical Institute under the Rural Development Ministry of Malaysia. The study findings identified the grit as the power of passion and perseverance not associated with long lasting job performance retention amongst Malaysian Technical Instructors. More broadly, this study provides a qualitative and dimensional understanding of the phenomena of grit as related to job performance retention.